Assessment of crop loss due to turcicum leaf blight caused by Exserohilum turcicum (Pass.) Leonard and Suggs in maize - SRIKANT KULKARNI; B.C. PATIL, S.I. HARLAPUR*, M.S. KULKARNI, (Indian Phytopathology, 2009)
The field trials on crop loss estimation due to turcicum leaf blight in maize were carried out during kharif seasons of 2003 and 2004. Significant loss in grain yield, stover yield, test weight and reduction in plant height, cob length, cob diameter and shelling percentage was observed in unprotected treatments in all the genotypes tested as compared to protected treatments. The avoidable yield loss in various genotypes ranged from 2.87 to 51.93 per cent with a mean of 14.51 per cent. The losses were directly proportional to the disease severity. The yield and yield attributing parameters showed a progressive increasing trend with an increase in number of fungicide sprays. Significant and negative correlation was established between blight severity under various spray schedules and grain as well as stover yields in both the years. This relationship was expressed by simple linear regression model.